Determination of residue of diazinon and carbosulfan in brinjal and quinalphos in yard long bean under supervised field trial - Kabir, KH; Rahman, MA; Ahmed, MS; Prodhan, MDH; Akon, MW (Bangladesh Journal of Agricultural Research, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The present study was undertaken to detect and quantify the left over residue of Diazinon and Carbosulfan in brinjal and Quinalphos in yard long bean and comparison between the detected residue level with maximum residue level (MRL) set by FAO (1970). Three supervised field trials (two for brinjal and one for yard long bean) were carried out sprayed with the field dose (1.5 ml/L of water) of Diazinon, Carbosulfan, and Quinaiphos. Samples were collected daily after spraying till residue were found. In case of Diazinon, left over residue was found upto 6 days after spray (DAS), and upto 3 DAS, the level of residue was above the MRL. Carbosulfan residue was detected till 7 DAS and the detected quantity of residue was above MRL upto 3 DAS. Left over residue of Quinalphos in yard long bean sample was detected upto 6 DAS and upto 4 DAS the level of residue was above the MRL. Key Words: Residue, Diazinon, Carbosulfan, Quinalphos. brinjal, yard long bean. doi:10.3329/bjar.v33i3.1609 Bangladesh J. Agril. Res. 33(3) : 503-513, September 2008